2022
DOI: 10.14348/molcells.2022.5005
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of CKD-504, a Novel Selective Histone Deacetylase 6 Inhibitor, in a Zebrafish Model of Neuromuscular Junction Disorders

Abstract: The neuromuscular junction (NMJ), which is a synapse for signal transmission from motor neurons to muscle cells, has emerged as an important region because of its association with several peripheral neuropathies. In particular, mutations in GARS that affect the formation of NMJ result in Charcot-Marie-Tooth disease and distal hereditary motor neuropathy. These disorders are mainly considered to be caused by neuronal axon abnormalities; however, no treatment is currently available. Theref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…However, except for ACY-1215, the present application range of other HDAC6 inhibitors is limited. Studies on ACY-241 ( Ray et al, 2018 ; Cosenza et al, 2020 ; Awad et al, 2021 ; Park et al, 2021 ) and KA2507 ( Tsimberidou et al, 2021 ) mainly focused on tumors, CKD-504 ( Choi et al, 2020 ; Ha et al, 2020 ; Jeong et al, 2022 ; Smith et al, 2022 ) focused on neurological diseases, and CKD-506 ( Choi et al, 2018 ; Park et al, 2020 ; Bae et al, 2021 ) focused on inflammatory diseases. Although ACY-241 and KA2507 show higher selectivity over ACY-1215 on HDAC6, its studies on other diseases needs further research ( Table 3 ).…”
Section: Future Perspectivementioning
confidence: 99%
“…However, except for ACY-1215, the present application range of other HDAC6 inhibitors is limited. Studies on ACY-241 ( Ray et al, 2018 ; Cosenza et al, 2020 ; Awad et al, 2021 ; Park et al, 2021 ) and KA2507 ( Tsimberidou et al, 2021 ) mainly focused on tumors, CKD-504 ( Choi et al, 2020 ; Ha et al, 2020 ; Jeong et al, 2022 ; Smith et al, 2022 ) focused on neurological diseases, and CKD-506 ( Choi et al, 2018 ; Park et al, 2020 ; Bae et al, 2021 ) focused on inflammatory diseases. Although ACY-241 and KA2507 show higher selectivity over ACY-1215 on HDAC6, its studies on other diseases needs further research ( Table 3 ).…”
Section: Future Perspectivementioning
confidence: 99%
“…In zebrafish, SV2 (synaptic vesicle protein 2) staining reveals synaptic vesicles in motor axons and terminals; thus, staining has been 2D) are opposed to postsynaptic α-BTX (bungarotoxin)-stained AChR clusters (red in Fig. 2D) [36,37]. We found that hRAB40B-Y83X-transformant zebrafish were labeled less often by both pre-and postsynaptic markers in the larval NMJs (Fig.…”
Section: Transient Transformation With Human Rab40b-y83x Induced Moti...mentioning
confidence: 79%
“…2D ) are opposed to postsynaptic α-BTX (bungarotoxin)-stained AChR clusters (red in Fig. 2D ) [ 36 , 37 ]. We found that hRAB40B-Y83X -transformant zebrafish were labeled less often by both pre- and postsynaptic markers in the larval NMJs ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Electrophysiologic misfiring and axonal transport defects are corrected in CMT2D motor neurons by tubastatin A and CKD-504 (124). Tubastatin A and CKD-504 improve deficient neurite outgrowth and defective neuromuscular junction maturation that are observed in zebrafish embryos where Gars is knocked down with splice-blocking antisense morpholino oligonucleotides (125).…”
Section: Multi-modal and Multi-indication Therapeutics For Motor Neur...mentioning
confidence: 99%